الروابط الحجاجية دراسة تداولية في شعر مصطفى بن زكري (Comprehensive Journal of Science, 2025)
Debating is considered a communication style or mean that fundamentally relies on showcasing arguments and proofs in order to persuade others. This research paper titled (Argumentative Connectives: A Pragmatic Study in the poetry of Mustafa Bin Zikry) is aimed to identify and discover the argumentative mechanisms used in Bin Zikry's poetry, in addition to, highlighting Libyan modern poetry in general and Bin Zikry's poetry in particular. This study will analyse the matter at hand from an argumentative persuasive standpoint, not just from an aesthetic point of view.
Keywords: Structure; Argumentation; Pragmatics; Links; bin Zekri.